2016
DOI: 10.5812/ijp.6129
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Serum and Urinary Matrix Metalloproteinase-9 Levels for the Early Detection of Renal Involvement in Children With Henoch-Schönlein Purpura

Abstract: BackgroundMatrix metalloproteinase-9 (MMP-9) is an enzyme implicated in the pathogenesis of renal diseases. Renal involvement is the principal cause of morbidity and mortality in children with Henoch-Schönlein purpura (HSP).ObjectivesThe aim of this study was to evaluate whether serum and urinary MMP-9 levels are associated with renal involvement in HSPPatients and MethodsWe evaluated 40 children with HSP (patient group) and 27 healthy volunteer children (control group). The patient group was divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[ 48 ] Other authors reported higher urinary MMP-9 activity in patients with CKD [ 38 40 ] and HSP with renal involvement. [ 49 ] Our study showed increased urinary MMP-9 excretions and decreased urinary MMP-9/TIMP-1 ratio. These results may suggest activation of ECM remodeling processes in children with SDNS and SRNS.…”
Section: Discussionmentioning
confidence: 59%
“…[ 48 ] Other authors reported higher urinary MMP-9 activity in patients with CKD [ 38 40 ] and HSP with renal involvement. [ 49 ] Our study showed increased urinary MMP-9 excretions and decreased urinary MMP-9/TIMP-1 ratio. These results may suggest activation of ECM remodeling processes in children with SDNS and SRNS.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, MMP-9 is co-localized in scattered neutrophils within diseased glomeruli in acute post-streptococcal glomerulonephritis [59]. In children with HSN, urinary MMP-9 levels are found significantly higher in comparison to controls and patients with just Henoch-Schönlein purpura [67]. In another study in children with CKD, urinary MMP-9 levels were significantly higher in comparison to controls, though, despite that, this study was not able to prospectively show a correlation of this finding with progressive CKD [68].…”
Section: Clusterin (Clu)mentioning
confidence: 99%
“…Some experimental studies found higher expression of TIMPs, particularly TIMP-1, in the renal tissue in the course of various kidney diseases [32,50]. This was confirmed in patients with CKD of different aetiology [23,51].…”
mentioning
confidence: 74%